Yan-Hou-Qing formula attenuates allergic airway inflammation via up-regulation of Treg and suppressing Th2 responses in Ovalbumin-induced asthmatic mice. (1st March 2019) - Cheng, Bao-Hui; Hu, Tian-Yong; Mo, Li-Hua; ma, Li; Hu, Wen-Hui; Li, Yi-Sheng; Liu, Zhi-Qiang; Qiu, Shu-Qi
Abstract: Ethnopharmacological relevance: Yan-Hou-Qing (YHQ), a Chinese medicine formula containing fourteen kinds of materials, has been designed for pharyngitis and cough treatment in Oriental medicine. In the present study, the anti-allergic effects and underlying mechanisms of YHQ in inhibition of airway hyper responsiveness (AHR) was explored in an ovalbumin (OVA)-induced allergic asthma mouse model. Materials and methods: BALB/c mice were sensitized by OVA and cholera toxin (CT) and challenged with OVA intranasally to induce allergic asthma mouse model. YHQ (200 mg/kg) was orally administered for 3 weeks from week-2 after OVA sensitization. The AHR and histological changes of lung tissues were evaluated by whole-body barometric plethysmography analysis and hematoxylin and eosin (H&E) staining, respectively. The serum concentration of OVA-specific IgE and T helper 2 (Th2) cytokines (IL-4 and IL-13) were determined by enzyme-linked immune sorbent assay (ELISA). Flow cytometry was performed to evaluate the percentage of CD4 + CD25 + Foxp3 + regulatory T cells (Treg) in the spleen. Results: The elevated AHR responses, heavier inflammatory cell infiltration and Th2 cytokines in allergic asthma group indicated Ovalbumin-induced asthmatic mouse models were built successfully. Compared to allergic asthma group, OVA-induced AHR responses and eosinophil infiltration in lung were improved significantly, and the productions of OVA-specific IgE and Th2 cytokines, IL-4 and IL-13, in the serum were also reduced dramatically after the treatment of YHQ. Moreover, YHQ treatment significantly increased the percentage of CD4 + CD25 + Foxp3 + Treg in OVA-induced allergic asthma mouse model. Conclusions: YHQ improves the allergic asthma related symptoms via promotion of CD4 + CD25 + Foxp3 + Treg and suppression of Th2 responses in mouse model, suggesting YHQ can be used as a potent agent to alleviate allergic asthma related symptoms. Graphical abstract: